PENGEMBANGAN MEDIA KOMIK DIGITAL PADA KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV SEKOLAH DASAR - Udur Lestari Silaban; Bunga Mulyahati; Maisarah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low reading comprehension skills of students and the unavailability of digital learning media specifically designed to support Indonesian Language learning in fourth-grade students at SD Negeri 9 Langsa, even though the school already had Chromebook facilities that had not been optimally utilized. This research aimed to develop digital comic media on the Ayo Menabung material and to determine its level of validity, practicality, and effectiveness in improving students’ reading comprehension skills. The method used was Research and Development (R&D) with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The subjects of this research were 13 fourth-grade students at SD Negeri 9 Langsa. Data collection techniques included observation, interviews, expert validation questionnaires (material, language, and media), teacher and student response questionnaires, and pretest-posttest scores. The results showed that the digital comic media obtained a material expert validation percentage of 91.11%, language expert 92.5%, media expert 100%, and question validation 96%, with an average of 94.90% in the “Very Valid” category. The practicality level based on teacher response was 95% and student response was 92.52%, with an average of 93.76% in the “Very Practical” category. The effectiveness test results showed an increase in learning completeness from 23.08% in the pretest to 100% in the posttest, with an N-Gain value of 0.77 in the “High” category and an N-Gain percentage of 77.97% in the “Very Effective” category. It can be concluded that digital comic media is feasible to use as learning media to improve elementary school students’ reading comprehension skills. Teachers are advised to utilize this digital comic media as an alternative learning media in the learning process.